If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -2x = 2x + 4 Reorder the terms: 6 + -2x = 4 + 2x Solving 6 + -2x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 6 + -2x + -2x = 4 + 2x + -2x Combine like terms: -2x + -2x = -4x 6 + -4x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 6 + -4x = 4 + 0 6 + -4x = 4 Add '-6' to each side of the equation. 6 + -6 + -4x = 4 + -6 Combine like terms: 6 + -6 = 0 0 + -4x = 4 + -6 -4x = 4 + -6 Combine like terms: 4 + -6 = -2 -4x = -2 Divide each side by '-4'. x = 0.5 Simplifying x = 0.5
| 24x+5=1 | | x^2-4x-4=0whatisx | | 16/2/3 | | 12x-13=2x+17 | | 15y-4=14+15y | | 1/4x+13=-1/4x | | 5x+3=19-4x+x | | 3e^3y=18 | | y+1=11/8(x+11) | | 2x^2+5+1=0 | | 25v^2+11=15 | | 4y^3-7y^2-16y-28=0 | | x^2-0.5x-36=37-y^2 | | 5x^4+31x^2+30=0 | | 3n+3=60 | | 3r^2-75= | | 2n+1=131 | | 2x-5y+27=0 | | v^4-12v+35=0 | | (128x)/(x^2-16)^2 | | h^2-17h= | | 15/x-15/x+2+2 | | 2x-4=3y | | 10.75=7.50+.25d | | b^2-12b-64= | | w^2-12w=-8 | | C=9/5f+32 | | 23-9x=131 | | a^4-9a^2+29=0 | | c+5d-12c= | | 2(lnx+1)=0 | | 0.10x+0.05(2-x)=0.10(5) |